You. The complete third season [videorecording (DVD)] - Badgley, Penn, 1986-; Pedretti, Victoria, 1995-; Burrows, Saffron; Tati Gabrielle, 1996-; Kepnes, Caroline, 1976- (Warner Bros., 2022)
Now married with a baby, Joe and Love have moved to a privileged Northern California enclave. Joe tries to commit to his new life but fears Love's lethal impulsiveness... and the woman he's always wanted might be living right next door. Breaking out of a basement cage is one thing, Escaping the prison of this picture perfect marriage may prove to be far more complicated.